Treatment of primary esophageal lymphomas: A review - Joe El Khoury; Remy Daou; Neal Kim; Josiane Bou Eid; Brandon Imber; Joachim Yahalom; Carla Hajj (Frontiers in Oncology)
Primary esophageal lymphoma is a rare malignancy that is difficult to diagnose and treat. While there have been significant advances in understanding the pathogenesis, clinical features, and treatment options, there is a lack of consensus on the most effective treatment approach. This literature review provides a comprehensive overview of the use of available treatment options for primary esophageal lymphoma, including surgery, radiotherapy, and chemotherapy. The review also highlights the current knowledge gaps that need to be addressed through further research. While no single treatment modality has emerged as a clear front-runner, a combination of these treatments may be the most effective approach in managing primary esophageal lymphoma, tailored to the histological subtypes.